Identity politics in India and Europe - Dusche, Michael; Sage eBooks (New Delhi ; London : SAGE, 2010)
The book examines present perceptions of East and West seen through the eyes of eminent scholars from India. The interviews presented here are set in the historical context of relations between Europe and the Muslim World and analysed from a theoretical angle drawing from theories of modernity, conceptions of justice and notions of identity politics.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Identity politics -- India; Identity politics -- Europe; Group identity -- India; Group identity -- Europe; Electronic books